The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1002/jor.22607
|View full text |Cite
|
Sign up to set email alerts
|

Particle‐induced osteolysis is not accompanied by systemic remodeling but is reflected by systemic bone biomarkers

Abstract: Particle-induced osteolysis is caused by an imbalance in bone resorption and formation, often leading to loss of implant fixation. Bone remodeling biomarkers may be useful for identification of osteolysis and studying pathogenesis, but interpretation of biomarker data could be confounded if local osteolysis engenders systemic bone remodeling. Our goal was to determine if remote bone remodeling contributes to biomarker levels. Serum concentrations of eight biomarkers and bone remodeling rates at local (femur), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…Indeed, the one longitudinal study included in this review showed that the bone resorption marker, CTX-1, was elevated early in patients undergoing TKA suspected to have loosened implants [17] and we recently also found that this marker was elevated early in a rat model [27]. A major challenge in longitudinal studies in patients is stratification into aseptic loosening/osteolysis and control groups, which can only occur long after initiation of the study because of the normal etiology of the disease.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, the one longitudinal study included in this review showed that the bone resorption marker, CTX-1, was elevated early in patients undergoing TKA suspected to have loosened implants [17] and we recently also found that this marker was elevated early in a rat model [27]. A major challenge in longitudinal studies in patients is stratification into aseptic loosening/osteolysis and control groups, which can only occur long after initiation of the study because of the normal etiology of the disease.…”
Section: Discussionmentioning
confidence: 97%
“…A second limitation is that we did not include animal studies in which biomarkers of aseptic loosening/osteolysis were studied [14,18,21,27] because only two of these studies included stable and loosened implants [18,27]. These two studies showed dramatic increases in serum CTX-1, OPG, cathepsin K, and PINP and depression of serum OC.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to storage at -80°C, blood was collected during euthanasia through the common iliac artery and centrifuged to separate serum at 2,000 rpm (425xg) for 5 min at 4°C as described previously [27, 28]. Serum OCN and VEGF levels were analyzed by using rabbit-specific enzyme-linked immunosorbent assay kits (Bioleaf Biotech, Shanghai, China) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…4,17,20,21,37,38 To assess the reproducibility of the model, we re-analyzed outcome data from the mouse marrow ablation model and the rat implant fixation model in which the animal strain, age, sex and experimental end points were comparable. Both mouse studies included females from FVB/NJ and BALB/cJ strains of the same age (10-11 weeks) with the same end point (bone volume/tissue volume, BV/TV) at 7 days post-marrow ablation.…”
Section: Reproducibility Of Surgery Outcomesmentioning
confidence: 99%
“…Blood is then centrifuged to separate the serum from blood solids and serum samples are stored at À 20 1C until analyzed. 38 …”
Section: Biomarkersmentioning
confidence: 99%